ANALISIS PEMASARAN BUAH LOKAL DI KALIMANTAN BARAT - Ekawati Ekawati; Ellyta Ellyta; Rahmatullah Rizieq (Jurnal Agribisnis Indonesia, 2014)
The final objective of this research is the completion of a local fruit marketing model to maintain local fruit products in the domestic market. Hence, the local fruit products always be a favorite product of West Kalimantan community. The specific objective of this research are (1) to identify the local fruit consumer profile, (2) to elaborate the local fruit consumer profile, (3) to identify and elaborate the local fruit consumer behavior, (4) to analyze the factors influencing consumer decision to buy local fruit. This study used descriptive survey method with 400 respondents by random selected method. The data would be analyzed by using multi-attribute models, while the relationship between factors to the consumption decision of local fruit would use rank Spearman correlation. The results stated that the decision to consume both local and imported fruit was more determined by their own decisions than determined by other people opinions. Consumers in Pontianak prefer to choose imported fruit rather than local fruit. In local fruit marketing, sellers had to consider four factors that correlate with the desire of consumers to buy the local fruits, namely: (a) taste, (b) quality/durability; (c) price and (d) packaging.